Representations of the warrior‐bishop in eleventh‐century Lotharingia. Issue 1 (19th January 2016) - Webb, J.R.
Abstract : Given the legal proscriptions against clerics bearing arms, the biographers of bishops who engaged in warfare faced a difficult task when they attempted to justify their heroes' military activities. In eleventh‐century Lotharingia, they did so by styling bishops as defenders of an oppressed populace. Two such biographies from Liège reach the opposite assessment of the warrior‐bishop. Their contrasting tone reveals changes in attitudes about the relationship between the church and warfare over the course of the eleventh century, when issues of episcopal power and righteous violence dominated the discourse, not only at Liège but far beyond it.